In-fibre second-harmonic generation with embedded two-dimensional materials - Ngo, Gia Quyet; Najafidehaghani, Emad; Gan, Ziyang; Khazaee, Sara; Siems, Malte Per; George, Antony; Schartner, Erik P.; Nolte, Stefan; Ebendorff-Heidepriem, Heike; Pertsch, Thomas; Tuniz, Alessandro; Schmidt, Markus A.; et al. (Nature Photonics, 2022)
Silica-based optical fibres are a workhorse of nonlinear optics, providing ready access to a range of nonlinear phenomena including solitons and self-phase modulation. However, they have one fundamental limitation: due to the amorphous nature of silica, they do not exhibit second-order nonlinearity, except for negligible contributions from surfaces. Here we demonstrate second-harmonic generation in functionalized optical fibres by using a monolayer of highly nonlinear MoS2 directly grown on the fibre’s core. The MoS2-functionalized fibre exhibits a second-order susceptibility (χ(2)) value of 44 pm V–1 and a second-harmonic generation conversion efficiency of 0.2 × 10–3 m−2 W−1. This approach is scalable and can be generalized to other transition metal dichalcogenides and a wide range of waveguide systems. Our results demonstrate a new approach towards efficient in-fibre second-harmonic generation sources and may establish a platform for χ(2)-based nonlinear fibre optics, optoelectronics, photonics platforms, integrated optical architectures and active fibre networks.
CRIS-Team Scopus Importer:2023-04-20